Pressure Drop Due to Cyclone Separator in Positive Dilute Phase Pneumatic Teff Grain Conveyor - L. D. Boset; Z. A. Debele; A. W. Koroso (Journal of Applied Fluid Mechanics)
Cyclone separators are commonly used in pneumatic conveyor systems due to their low cost and ability to separate solid particles from gas streams. Understanding pressure drop in cyclone separators is crucial for designing, developing, and optimizing efficient cyclone separators for pneumatic conveyors. The swirling motion within the cyclone during particle-gas separation can cause a pressure drop in the pneumatic conveyor. This study investigates the pressure drop across cyclone separators in pneumatic conveyor systems for Teff grain, both experimentally and computational fluid dynamics (CFD) with discrete particle modeling (DPM) simulation. The study utilized the Lapple cyclone separator model and examined the effects of varying cyclone size (0.75D, 0.9D, and 1D for D=200mm), inlet air velocity (10m/s, 14m/s, 18m/s, 22m/s), and material mass flow rate (0.009kg/s, 0.03kg/s, 0.044kg/s, 0.067kg/s) on the pressure drop across the cyclone separator. The results show that there is strong agreement between experimental and CFD-DPM simulation results. The simulation results accurately represent experimental results, with R-squared value of 0.99 and a residual sum of squares of 38.018. Furthermore, the best curve fit was obtained between the power losses due to pressure drop across the cyclone separator and air mass flow rate. These findings demonstrate that the pressure drop and associated power losses across cyclone separators in pneumatic Teff grain conveyors can be effectively determined using both experimental and simulation methods. This finding can inform the design and optimization of efficient cyclone separators for pneumatic Teff grain conveyor systems.